2004
DOI: 10.1083/jcb.200408124
|View full text |Cite
|
Sign up to set email alerts
|

Vesicles carry most exocyst subunits to exocytic sites marked by the remaining two subunits, Sec3p and Exo70p

Abstract: Exocytosis in the budding yeast Saccharomyces cerevisiae occurs at discrete domains of the plasma membrane. The protein complex that tethers incoming vesicles to sites of secretion is known as the exocyst. We have used photobleaching recovery experiments to characterize the dynamic behavior of the eight subunits that make up the exocyst. One subset (Sec5p, Sec6p, Sec8p, Sec10p, Sec15p, and Exo84p) exhibits mobility similar to that of the vesicle-bound Rab family protein Sec4p, whereas Sec3p and Exo70p exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
345
2
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(377 citation statements)
references
References 50 publications
25
345
2
3
Order By: Relevance
“…Interestingly, Sec3 and Exo70 were speculated to localize to both PM and secretory vesicles (Boyd, Hughes et al 2004). Exocyst assembly on endosomes is driven by the Sec15 subunit which is a Rab11 effector (Zhang, Ellis et al 2004) that directly interacts with the exocyst subunits Sec10, Exo84 and Exo70.…”
Section: Exocyst Tethering In Endosomal Exocytosis Is Regulated By Enmentioning
confidence: 99%
“…Interestingly, Sec3 and Exo70 were speculated to localize to both PM and secretory vesicles (Boyd, Hughes et al 2004). Exocyst assembly on endosomes is driven by the Sec15 subunit which is a Rab11 effector (Zhang, Ellis et al 2004) that directly interacts with the exocyst subunits Sec10, Exo84 and Exo70.…”
Section: Exocyst Tethering In Endosomal Exocytosis Is Regulated By Enmentioning
confidence: 99%
“…One key question yet to be resolved is how the exocyst itself associates with the PM. Using fluorescence recovery after photobleaching (FRAP) analyses and immunoelectron microscopy, Boyd et al (2004) have shown that Exo70 is stably localized to the yeast bud tip membrane and remains polarized even when the actin cables are disrupted, suggesting that Exo70 is a candidate in this complex involved in membrane targeting of the exocyst. In Madin-Darby canine kidney (MDCK) cells, extragenically expressed GFP-tagged Exo70 is localized to the PM near cell-cell contacts, suggesting that Exo70 may mediate PM association independent of the rest exocyst components in these cells (Matern et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Exocysts are complexes of proteins with some rod-like domains consisting of helical bundles (Munson and Novick, 2006) that are carried by secretory vesicles and target them to plasmalemmal exocytotic sites (Guo et al, 1999), which are marked by other units of the exocysts (Boyd et al, 2004). …”
Section: Discussionmentioning
confidence: 99%